A study on the construction of body fat percentage percentile curve for adults aged 20–79 in China - Tu, Chunjing; Pan, Qi; Zou, Jinhui; Liao, Lihong; Chen, Xiaolong; Li, Yuyu; Pu, Xinzhe; Ding, Yuanyuan; Luo, Xiwen (Frontiers in Public Health, 2025)
ObjectiveTo establish age-specific Body Fat Percentage (BFP) percentile curves for Chinese adults aged 20–79 years, providing a reference tool for accurate BFP assessment and the prediction and prevention of obesity.MethodsBased on the data from 29,064 individuals obtained through the National Physical Fitness Surveillance (NPFS) in four provinces across China (East, South, West, and North), GAMLSS (Generalized Additive Models for Location Scale and Shape) was used to construct gender- and age- specific BFP percentile curves, and obesity cut-off points were defined.ResultsFirst, age-specific BFP percentile curves were established for the P3, P5, P10, P25, P40, P50, P60, P75, P90, P95, P97 percentiles, and standardized Z-score curve for-3SD, −2SD, −SD, 0SD, +1SD, +2SD, and +3SD. Second, among Chinese adults aged 20–79 years, BFP increased with age before decreasing, with the peak occurring earlier for men than for women. The inflection points for men and women occurred at ages 65 and 73, respectively, with a difference of 8 years. Across all age groups, BFP percentiles for men were consistently lower than those for women. Third, the 75th percentile was identified as the cut-off point for BFP in defining obesity. The cut-off BFP for men across age groups ranged from 27.8–33.5%, and the cut-off for women ranged from 29.2–36.8%.ConclusionThe age-specific BFP percentile curves formulated in this study allow for the personalized and precise assessment of obesity in middle-aged and older adults. They also enable early prediction and risk warning of obesity in the older age groups. The findings support national goals such as “early intervention” and “precise assessment” and are recommended for use in practical settings to evaluate BFP and obesity in middle-aged and older adult populations in China.